SOCIAL AND LINGUISTIC DIVERSITY IN MODERN BRITAIN THROUGH THE CONTEMPORARY DETECTIVE NOVEL: Received: 30th April 2021; Revised: 3rd August 2021, 4th December 2021; Accepted: 17th December 2021 - Ihata, Anne C (PEOPLE: International Journal of Social Sciences, 2021)
The aim of this paper is twofold: to examine how present-day detective novels reflect Britain’s geographic, social, and linguistic diversities in a way that perhaps no other single genre of fiction does, and to consider how this differs from those works that are generally regarded as the classic examples in this field. Current writing in this category exhibits various characteristics that distinguish these works from older works, and these features are reviewed and possible reasons for the recent diversification considered. However, attention is also paid to the fact that there are, nonetheless, modern works which seem to more closely follow the model of the ‘traditional’ detective story. It is possible that there are two distinct trends involved, which overlap in some areas to complement each other in terms of filling the various niches in the readership of detective fiction. This is essentially an empirical study, based on the author’s extensive reading of detective fiction, both classic and contemporary, over a number of years. Although much of this was originally done as a hobby, personal observation of the extremely wide-ranging nature of the modern British detective novel led to a desire to examine the diversity of the genre in detail.